2016
DOI: 10.1097/fpc.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of early weight gain during psychotropic treatment using a combinatorial model with clinical and genetic markers

Abstract: These results may help to implement genetic testing before starting psychotropic drug treatment to identify patients at risk of important WG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…We also find an association between BMI and number of weight gain drugs prescribed. A recent study predicted early weight gain in individuals starting initial treatment with weight-promoting psychotropic drugs, and found that age and baseline BMI were significantly associated with strong weight gain 64 . In contrast to our results, they found that addition of genetic data (18 genes previously associated with weight gain) improved model performance 64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also find an association between BMI and number of weight gain drugs prescribed. A recent study predicted early weight gain in individuals starting initial treatment with weight-promoting psychotropic drugs, and found that age and baseline BMI were significantly associated with strong weight gain 64 . In contrast to our results, they found that addition of genetic data (18 genes previously associated with weight gain) improved model performance 64 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study predicted early weight gain in individuals starting initial treatment with weight-promoting psychotropic drugs, and found that age and baseline BMI were significantly associated with strong weight gain 64 . In contrast to our results, they found that addition of genetic data (18 genes previously associated with weight gain) improved model performance 64 . We tested SNPs previously associated with BMI, in addition to polygenic risk scores and found that adding candidate genes did not improve model performance relative to PRS alone.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the genetic findings with clinical risk factors for weight gain has resulted in modest improvements when compared to only using clinical factors. Whereas, in one study genetic data (SNPs from GWA studies of BMI and candidate gene studies) increased the prediction accuracy compared to using clinical data alone ( 150 ), in another study adding data from PRSs did not improve the prediction of weight gain compared to the clinical information ( 148 ).…”
Section: Outcome Prediction: Current Evidencementioning
confidence: 98%
“…Selective CB 1 receptor antagonist SR141716A (rimonabant) ameliorates diet-induced obesity of mice through enhancement of fatty acid oxidation and energy expenditure in white adipocytes (Jbilo et al, 2005), or modulating macrophage inflammatory mediators via gut microbiota alterations (Mehrpouya-Bahrami et al, 2017). Clinical trials proved that rimonabant decreased body weight and waist circumference in overweight or obese patients (Van Gaal et al, 2005;Pi-Sunyer et al, 2006). The 3813G allele at the exon 4 of CNR1 is associated with obesity-related phenotypes like waist circumference and subscapular skinfold thickness in adult men (Russo et al, 2007).…”
Section: The Cannabinoid 1 Receptormentioning
confidence: 99%
“…A multigene risk-model has showed promising results of predicting antipsychotic-induced weight gain (Tiwari et al, 2014). Moreover, the combinatorial model of genetic and clinical data could help to identify patients at high risk for early weight gain (Vandenberghe et al, 2016). On the other hand, the more we know about the mechanism of the metabolic side effects of atypical antipsychotics, the better we can tackle with this troublesome adverse drug reaction.…”
Section: Future Perspectivementioning
confidence: 99%